Wisata Virtual Penyu Untuk Medukung Pariwisata Bahari di Pantai Serang, Kabupaten Blitar - Bambang Semedi; Bagyo Yanuwiadi; Marjono Marjono; Putri Dila Nur Fatimah Afionita; Novia Fara Diza; Setya Nuri Fatma Dewi (Universitas Muhammadiyah Surakarta, 2022)
Some coast at south of East Java have been known as sea turtle nesting sites. One of that site is at Serang Beach, Regency of Panggungrejo, Blitar. Since a long time ago, Serang Beach is a favorite location for holiday because it has many beautiful and interesting spots. But, there is an educational spot, sea turtle conservation which not widely known by tourists. It shows that the publication about the existence of sea turtle still not enough. However, people must know about it because the population of sea turtle in nature is getting worse. The more people know about sea turtle will increasing the awareness to protect sea turtle. Therefore it is necessary to create an online publication during the global pandemic of COVID-19. The best solution is create a virtual tour about sea turtle at Serang Beach. Virtual tour is the best way to introduce the existence of sea turtle and give opportunities to return tourism activites which have been stucked for about two years because of COVID-19 pandemic. There are three main activities of this program including preparation, implementation, and evaluation. Preparation step includes literature studies, surveys to Serang Beach as program locations, permits and interviews with stakeholders, plotting and scripting session for virtual tourism videos. Implementation step includes video recording for virtual tour about sea turtle at Serang Beach, video editing, video publication on social media YouTube, and mentoring with partners through focus group discussions. Video virtual tour about sea turtle at Serang Beach on YouTube received positive responses from the viewers. The presence of virtual tour about sea turtle at Serang Beach increases people knowledge about sea turtle and encourage them to holiday at Serang Beach.